IMPLEMENTASI TEKNOLOGI INFORMASI PADA STRATEGI PEMASARAN AGRIBISNIS PETERNAKAN UNGGAS MENGGUNAKAN ANALISA SWOT - Retnasari, Tri (www.bsi.ac.id, 2016)
Agribusiness can be divided into three sectors are interdependent economically , the sector inputs (input ) , production ( farm) and sector output ( output ) . Support for information technology can be a measure of progress and processing the data into information becomes faster and is performed automatically . Many agribusiness during this period utilizing technology support in the form of information systems , with the aim to facilitate the activities , one of which is the CV . Kurnia Mitra Mandiri . As one of the agribusiness engaged in farming, has not fully able to provide complete information so as to implement the information technology necessary to design a good information system architecture . Prior to the implementation of IT , do the analysis first using SWOT analysis . From this analysis, the next ditahap do plan to use information technology in terms of marketing , production , product development , and finance. Keywords: Agribusiness, Information Technology, SWOT.